The Theory of Planned Behaviour (TPB): Development, Validity and Reliability of an Instrument for measuring its Explanatory Constructs in Teacher Training Colleges in Tanzania - Luhamya, Aloysious N.; Bakkabulindi , Fred E. K.; Muyinda , Paul B . (African Journal of Education,Science and Technology (AJEST), 2018)
The Theory of Planned Behaviour (TPB) stipulates that actual behaviour (AB) is predicted by behaviour intention (BI) and perceived behavioural control (PBC). In turn BI is predicted by attitude toward behaviour (ATB), subjective norm (SN) and PBC. ATB in turn, is predicted by behavioural beliefs and outcome evaluation (bboe); SN is predicted by normative beliefs and motivation to comply (nbmc); and PBC is predicted by control beliefs perceived facilitation (cbpf). Three question guided this study: To what extent was each of the explanatory constructs of TPB valid and reliable? Were the constructs independent? To what extent did the explanatory constructs in the TPB form a seven-factor structure? A sample of 184 from among educators in seven teacher training colleges (TTCs) in Tanzania responded to a questionnaire. Factor analysis, Cronbach alpha, and Pearson linear correlation were used for analysis. Hence, except the items of one construct (cbpfi), all the items of each of the remaining constructs were valid. However the constructs were highly inter-correlated. Lastly, only two constructs (PBC & cbpfi) were distinct. Hence the recommendation that researchers continue refining the explanatory constructs of the TPB.